MICROCREDIT IN BRAZIL: AN EXPLORATORY STUDY ON THE IMPACT OF MICROCREDIT ON THE BRAZILIAN ECONOMY - Pereira da Silva Leão, Airton; Borges Alves Pessoa , Solange; Melo Costa Simões, Valéria; Guimarães Bezerra, Thayná (Revista Gênero e Interdisciplinaridade, 2026)
Introduction: Microcredit has been analyzed as a suitable alternative for generating employment and income for the most needy population, as it has allowed the development of economic activities by these individuals, offering a possibility of income generation in a country where unemployment is quite prevalent. Objective: To explore the impact of microcredit on the Brazilian economy. Methodology: This study is a bibliographic research. The methodological approach of the bibliographic review is carried out in eight stages such as: choice of the theme, search for the database to be analyzed, interpretation of the studies, exclusion of articles that did not fit the research, evaluation of the studies included in the research, creation of a sample table reporting the number of clients served by the Crediamigo program of Banco do Nordeste in 2021, creation of a sample table reporting amounts disbursed to clients in 2021, and interpretation and presentation of the results. Results: Considering all the research and analysis of the context of this article, it is clear how relevant the study of microcredit is and how much it has directly influenced the Brazilian economy and how much it has grown. It was possible to understand the magnitude of microcredit in Brazil and how many people have had their lives transformed through microcredit programs. In 2020 and 2021, the number of unemployed people grew even in the face of the Covid-19 pandemic, and entrepreneurship continued to develop. Conclusion: Microcredit has increasingly shown how important and significant it is, evidenced by the amounts applied by a program that serves only one region of a country that is continental in size. Therefore, microcredit is a valuable asset for the population that depends solely on itself to support its family.